Cytotoxic Aaptamines from Malaysian Aaptos aaptos. - Shaari, Khozirah; Kee, Cheng Ling; Mat Rashid, Zalilawati; Tan, Pei Jean; Abas, Faridah; Mohd Raof, Salahudin; Zainal, Zurina; Lajis, Nordin; Mohamad, Habsah; Ali, Abdul Manaf (MDPI, 2009)
In a preliminary screen, Aaptos aaptos showed significant cytotoxic activity towards a panel of cell lines and was thus subjected to bioassay-guided isolation of the bioactive constituents. In addition to the known aaptamine, two new derivatives of the alkaloid were isolated from the bioactive chloroform fraction of the crude methanolic extract. Detailed analysis by NMR and mass spectroscopy enabled their identification to be 3-(phenethylamino)demethyl(oxy)aaptamine and 3-(isopentylamino)demethyl(oxy) aaptamine. The cytotoxic activities of the three alkaloids were further evaluated against CEM-SS cells.